The effectiveness of massage therapy combined with stretching toward blood pressure of elderly people with hypertension - Enggista Hendriko Delano; Wara Kushartanti; Abiyyu Amajida; Muhammad Fatih Humam; Sabda Hussain As Shafi (Jurnal Keolahragaan, 2022)
The high case of hypertension in the elderly requires curative action. One of the efforts to prevent and treat hypertension is by nonpharmacological methods with massage therapy combined with stretching. This research aimed to discover the effectiveness of massage therapy followed by stretching toward the blood pressure of older people with hypertension. Employing a Quasi Experiment design with one group pretest-posttest, the study involved 25 people who had hypertension With 14 of which were selected using specific criteria. The research used Digital Sphygmomanometer to measure blood pressure. The treatment given to the samples was massage therapy for hypertension with the Ali Satia Graha method for about 20 minutes followed by stretching for about 20 minutes. The data analysis technique of this research was the paired t-test, which aimed to find the significant gap. The research findings showed that the systole value before getting the treatment was 158.36 mmHg, and after getting the treatment, it decreased to 137.93 mmHg (12,90%) with a significance value of 0.000 0.05. Diastolic blood pressure before getting the treatment was at 98.07 mmHg, and after getting the treatment, it dropped to 86.79 (11,50) mmHg with a significance value of 0.000 0.05. Hence, it could be concluded that Ali Satia Graha massage method with stretching effectively decreased the blood pressure of older people with hypertension